Trace metal and carbon isotopic variations in cave dripwater and stalagmite geochemistry from northern Borneo - Judson W, Partin; Kim M, Cobb; Jess F, Adkins; Andrew Alek, Tuen; Brian, Clark (AGU and Geochemical Society, 2013)
[2] Stalagmites are valuable archives of terrestrial paleoclimate because they form in karst systems located around the world, can be absolute-dated, and afford high-resolution reconstructions on glacialinterglacial timescales. Stalagmite oxygen isotopic composition (18O) is the primary proxy used for stalagmite paleoclimate reconstructions because it reflects changes in rainfall 18O that are related to rainfall amount [Dansgaard, 1964; Rozanski et al.